USULAN PENGGUNAAN METODE FAULT TREE ANALYSIS UNTUK PENURUNAN KECELAKAAN KERJA PADA PT. INOAC POLYTECHNO INDONESIA (Universitas Esa Unggul, 2015)
AbstractThe persistently high number of accidents in PT. Inoac Polytechno Indonesia has the goal to provide corrective suggestions and recommendations for action to minimize the causes of accidents by using fault tree analysis (FTA) with supporting tools that a causal diagram (Cause and Efect Analysis), pareto chart, digram matrik. An analysis of the problem of workplace accidents finds that there are nine types of work accidents is exposed to a chemical liquid, foaming machines hit, nicked blade cutter, explosion, terpleset, burned, crushed foam, sandwiched conveyor, electric voltage shock. From the data using Pareto diagram known mixing machine blast of heat that is by 20.6%. Through the method of cause and effect analysis obtained dominant factors that cause the problems that occurred in the machine, man, method, materials, environment. The results of the method in the matrix diagram can be several factors such as the machine (the machine age, error), human (not running S.O.P, less examination), the environment (heat). Results using fault tree analysis known root problems that occur in the engine explosion mixing heat that is quality material ugly, maintenance schedules irregular, the stock of spare parts was empty, to pay more for training, pressure from superiors, reach production targets, self-awareness is lacking, and lack of ventilation. Preventive action proposals and recommendations for action to prevent problems occurring that is necessary to stock spare parts, creating a list of treatments is based on preventive maintenance, determination of useful life for tools and components based on the load received, adding cooling systems or air circulation. Keywords : Occupational Health and Safety (K3), work accidents, Pareto charts, Cause and Effect Diagram, Diagram matrix, Fault Tree Analysis (FTA) AbstrakMasih tingginya angka kecelakaan kerja di PT. Inoac Polytechno Indonesia memiliki tujuan untuk memberikan usulan perbaikan serta rekomendasi tindakan untuk meminimasi penyebab kecelakaan kerja dengan menggunakan fault tree analysis (FTA) dan dengan tools pendukung yaitu diagram sebab akibat (Cause and Efect Analysis), pareto chart, dan diagram matrik. Hasil analisa pada permasalahan kecelakaan kerja diketahui terdapat 9 jenis kecelakaan kerja yaitu terkena cairan kimia, terbentur mesin foaming, tergores mata pisau pemotong, ledakan, terpleset, terbakar, tertimpa foam, terjepit conveyor, tersengat tegangan listrik. Dari data dengan menggunakan diagram pareto diketahui ledakan mesin mixing heat yaitu sebesar 20,6%. Melalui metode cause and efect analysis didapatkan faktor-faktor penyebab dominan dalam permasalahan yang terjadi yaitu mesin, manusia, metode, material, lingkungan. Hasil dengan metode diagram matrik di dapat beberapa faktor seperti mesin (umur mesin, eror), manusia (tidak menjalankan S.O.P, kurang pemeriksaan), lingkungan (panas). Hasil menggunakan fault tree analysisis diketahui akar permasalahan yang terjadi pada ledakan mesin mixing heat yaitu kulitas material jelek, jadwal perawatan tidak teratur, stok sparepart kosong, mengeluarkan biaya lebih untuk pelatihan, adanya tekanan dari atasan, mengejar target produksi, kesadaran diri yang kurang, dan kurangnya ventilasi. Tindakan usulan pencegahan dan rekomendasi tindakan untuk mencegah masalah yang terjadi yaitu diperlukan adanya stok sparepart, pembuatan daftar perawatan berdasarkan preventive maintenance, penentuan umur pakai untuk alat maupun komponen berdasarkan beban yang diterima, menambahkan sistem pendingin atau sirkulasi udara. Kata kunci : Keselamatan dan Kesehatan Kerja (K3), kecelakaan kerja, Pareto chart, Cause and Effect Diagram, Diagram matrik, Fault Tree Analysis (FTA)